Metal-free catalysis on the reactions of nitric acid with aliphatic aldehydes: A new potential source of organic nitrates. (15th April 2023) - Bai, Feng-Yang; Chi, Tai-Xing; Liu, Xiang-Huan; Meng, Ting-Ting; Ni, Shuang; Zhao, Zhen
Abstract: The photochemical reaction of peroxy radical (RO2 ·) and NO has been identified by field and forest studies as important source of organic nitrates (RONO2 ) in the atmosphere. However, this traditional pathway is not sufficient to explain the high concentration of RONO2 . Hence, a new source of the tropospheric RONO2 from the dark reactions of nitric acid (HNO3 ) with aliphatic aldehydes (C1 –C5 ) under catalysis is provided and examined for the first time by high-level quantum chemistry. The findings show that the reaction between HCHO and HNO3, which produces HOCH2 ONO2, can be catalyzed by a series of metal-free catalysts (NH3, CH3 NH2, CH3 NHCH3, H2 O, HNO3, H2 SO4, HCOOH, HOOCCOOH). At 296 K, the effective rate constant for the bimolecular HNO3 –HCHO reaction under the catalysis of CH3 NH2 or CH3 NHCH3 can be sufficiently accelerated by 5–8 order of magnitudes through this new loss pathway for HNO3 or HCHO to become competitive with the conventional loss pathway for their photochemical reactions with ·OH radical. Significantly, this new HOCH2 ONO2 formation pathway from the dark reaction of HCHO with CH3 NH3 + NO3 − /(CH3 )2 NH + NO3 − was more favorable than the recognized source of RO2 · with NO. Efficient catalysis performance of CH3 NH2 and CH3 NHCH3 is mainly attributed to their excellent proton receptivity capacity by activating the O–H bond of HNO3 to form stable organic nitrates (CH3 NH3 + NO3 − and (CH3 )2 NH + NO3 − ) in the rate-determining step transition states. In the case of only considering the barrier, H2 SO4 is the best catalyst among the investigated inorganic and organic acids, and dicarboxylic acid (HOOCCOOH) is stronger than monocarboxylic acid HCOOH in facilitating the RONO2 formation reaction. These new findings deepen our understanding on the unexpected source of organic nitrate and loss pathway of HNO3 or HCHO under catalysis in highly polluted regions. Graphical abstract: Image 1 Highlights: Kinetics and mechanism for reactions of HNO3 with C1 –C5 aliphatic aldehydes were studied. Role of water, acids, and alkalies on the HNO3 /HCHO reaction were analyzed. A new loss pathway for HCHO was identified via amine-catalyzed HNO3 /HCHO reaction. An unexpected source of RONO2 with the help of catalysts was proposed and verified. The proposed new source of RONO2 was more favorable than that of RO2 ·/NO reaction.